Data supporting 'An exploration of customers satisfaction with water and wastewater services in the UK' - Smith, Heather M.; Tian, Kang; Goodwin, Daniel; Gallagher, Elaine (Cranfield University, 2023)
This dataset underpins the paper entitled 'An Exploration of Customers' Satisfaction with Water and Wastewater Services in the UK' in the journal Water Economics and Policy. Data was collected through an online survey administered in Qualtrics. The data is in .sav format which is suitable for the SPSS statistical software. For further info contact the corresponding author.
Keywords: public perceptions'; 'Water and Wastewater'; 'Customer satisfaciton'; 'Communication'; 'trust'